Mobile Application Searching of the Shortest Route on Delivery Order of CV. Alfa Fresh With Brute Force Algorithm - Indri Ariyanti; M. Aris Ganiardi; Ulsa Oktari (Logic : Jurnal Rancang Bangun dan Teknologi, 2019)
Traveling Salesman Problem is a problem solving used in finding the shortest route to visit all nodes at once and then return to the initial node. Troubleshooting of the Traveling Salesman Problem using the Brute Force algorithm. The object of this research is the courier at CV. Alfa Fresh. The Brute Force algorithm provides a solution for Traveling Salesman Problems to select and determine the shortest routes to deliver orders from the office to the destination. The Brute Force algorithm is an algorithm that is used to match patterns with all routes to be traversed to find the shortest route pattern. The Brute Force algorithm works by enumerating all possible candidates. With this application can facilitate the courier in determining the closest route from the position of the courier.